Case Report: Emergency CABG Following Failure of PTCA in a COVID-19 Patient - Romiti, Silvia; Totaro, Marco; Laderchi, Amalia; Peruzzi, Mariangela; Vinciguerra, Mattia; Greco, Ernesto (Frontiers in Cardiovascular Medicine, 2021)
The coronavirus disease 2019 (COVID-19) pandemic outbreak, caused by severe acute respiratory syndrome coronavirus-2 (SARS-Cov-2) is affecting people worldwide representing a public health emergency. The effect of concomitant COVID-19 on patients who underwent cardiac surgery using cardiopulmonary bypass (CPB) is still undefined. Both SARS-Cov-2 infection and CPB can develop a cytokines storm and haemostatic disarrangements leading to acute respiratory distress syndrome (ARDS) and post perfusion lung syndrome, respectively. SARS-Cov-2 infection may trigger and exacerbate post-inflammatory state after CPB resulting in higher risk of post-surgical adverse outcomes. International guidelines lack to provide standard management protocols for pre-operative COVID-19 patients requiring non deferrable cardiac surgery intervention. We present a report of a successful coronary artery bypass grafting (CABG) emergency operation in a COVID-19 patient, who presented unstable angina and coronary artery dissection during cardiac catheterization and percutaneous transluminal coronary angioplasty (PTCA).